Pengembangan Snack Bar Berbahan Tepung Porang dan Tepung Kacang Hijau Sebagai Makanan Tambahan Olahraga: Development of a Porang (Amorphophallus muelleri) and Mung Bean (Vigna radiata) Based Snack Bar as a Functional Sports Supplement - Shidqi Rasyid Abdurrahim; Fachruddin Perdana; Rakhmi Setyani Sartika (Universitas Airlangga, 2025)
Background: Inadequate nutritional intake leading to energy deficiency in athletes can significantly impair athletic performance. Prior studies involving 11 PS TIRA PERSIBO Bogor athletes revealed that their intake of energy and macronutrients was below 80% of recommended levels. Therefore, the development of snack bars is essential to supplement daily nutritional requirements. Objectives: This study aimed to develop a snack bar formulation utilizing porang flour and mung bean flour as a potential sport supplement. Methods: In this experimental study, the nutritional content of three snack bar formulations was evaluated with varying compositions of porang flour and mung beans flour (designated as F1 [4:8], F2 [6:6], F3 [8:4]). A single-factor Complete Randomized Design (CRD) was employed with three replications. Sensory properties were assessed via hedonic and hedonic quality tests involving 20 semi-trained panelists. Results: The hedonic test results indicated significant differences (p-value < 0.05) in color, taste, texture, aftertaste, and overall acceptability across all formulation. Similarly, the hedonic quality test results showed significant differences (p-value < 0.05) in all assessed parameters. Proximate analysis, as well as fiber and sugar content assays, demonstrated significant differences (p-value < 0.05) between formulas. Based on a weighing scoring system, F1 was identified as the optimal formulation. The F1 snack bar consists of 5.3% (5.3 g) protein, 5.2% (5.2 g) fat, 21.6% (21.6 g) carbohydrates, 8.4% (8.4 g) fiber, and provides 154 kcal of energy per 100 g. According to BPOM regulations, this product is classified as a source of protein and high-fiber food. Conclusions: The developed snack bars are recommended for consumption during the post-exercise recovery phase due to their high fiber content and protein-to-carbohydrate profile.